Comparison of vertical bone resorption following various types of autologous block bone grafts - Hyejin Koo; Junghye Hwang; Byung-Joon Choi; Jung-Woo Lee; Joo-Young Ohe; Junho Jung (SpringerOpen, 2023)
Abstract Background This study aims to measure and compare the differences in vertical bone resorption after vertical augmentation using different types of autologous block bone. Methods Data were collected from 38 patients who had undergone vertical ridge augmentation using an autologous block bone before implant insertion. The patients were divided into three groups based on the donor sites: ramus bone (RB), chin bone (CB), and iliac crestal bone (IB). Results The surgical outcome of the augmentation was evaluated at the follow-up periods up to 60 months. In 38 patients, the mean amount of vertical bone gain was 8.36 ± 1.51 mm in the IB group, followed by the RB group (4.17 ± 1.31 mm) and the CB group (3.44 ± 1.08 mm). There is a significant difference in vertical bone resorption between the groups (p < 0.001), and the RB group demonstrated significantly lower resorption than the CB and IB groups (p = 0.011 and p < 0.001, respectively). The most common postoperative complications included neurosensory disturbance in the CB graft and gait disturbance in the IB graft. Out of the 92 implants inserted after augmentation, four implants were lost during the study period, resulting in an implant success rate of 95.65%. Conclusions The RB graft might be the most suitable option for vertical augmentation in terms of maintaining postoperative vertical height and reducing morbidity, although the initial gain was greater with the IB graft compared to other block bones.